Adherence to customized vestibular rehabilitation therapy: influencing factors and clinical implications in vestibulopathy - Yeon Hee Im; Hyun Jin Lee; Eun-Ju Jeon (Frontiers in Neurology)
ObjectiveCustomized vestibular rehabilitation therapy (CVRT) is an effective treatment approach for various vestibular disorders. However, low adherence significantly limits its efficacy, and factors influencing adherence remain underexplored. This study aimed to identify factors affecting adherence to CVRT across major vestibulopathy categories, including acute unilateral vestibular hypofunction (AUVH), chronic unilateral vestibular hypofunction (CUVH), and bilateral vestibular hypofunction (BVH).MethodsA retrospective analysis of 90 patients who were prescribed four sessions of CVRT and underwent the therapy was conducted. Patients were classified as adherent (≥3 sessions) or non-adherent (≤2 sessions). Demographic characteristics, baseline questionnaire scores, and vestibular function test (VFT) results were compared. Change in questionnaire scores and VFT results before and after CVRT, as well as mid-treatment follow-up questionnaire scores were analyzed.ResultsAdherence rates were highest in CUVH (86.7%) and lowest in BVH (46.2%). Among patients with AUVH, poor functional reach test scores were significantly associated with lower adherence (p = 0.045). In the CUVH category, patients with mild dizziness in the initial questionnaire were non-adherent (p = 0.019). CVRT improved subjective dizziness symptoms and VFT parameters, with the greatest gains observed in AUVH. However, no significant differences in symptom improvement were found between adherent and non-adherent patients. Patients whose symptoms improved rapidly to a mild degree after starting the CVRT were more likely to be non-adherent, with this tendency being especially pronounced in those with AUVH.ConclusionAdherence to CVRT varies by vestibulopathy category and is influenced by baseline symptom severity. Tailoring CVRT strategies based on individual clinical profiles may enhance adherence and optimize therapeutic outcomes.